PENGARUH TAX KNOWLEDGE DAN GENDER TERHADAP TAX COMPLIANCE WAJIB PAJAK PRIBADI DI KANTOR PELAYANAN PAJAK PRATAMA KOTA TEGAL - Dewi Apriani; Teguh Budi Raharjo; Agnes Dwita Susilawati (CAPITAL: Jurnal Ekonomi dan Manajemen, 2018)
Tax is a source of state revenue. Tax complience is an important factor for increasing tax revenues. Gender aspects are also matters related to the behavior of taxpayers. The purpose of this research is: to determine the influence of tax knowledge and gender together on tax compliance, to determine the effect of tax knowledge on tax compliance, and to determine the effect of gender on tax. This study uses qualitative research methods with a form of survey conducted at the Primary Tax Service Office, totaling 17,232 taxpayers. Based on the results of partial testing using the t test results obtained for gender with a significance value of 0.007 at the 0.05 level, this means that the H3 hypothesis is accepted, meaning that gender has a significant effect on taxpayers' personal tax compliance and3. the results of calculations using the F test obtained the results of a significance value of 0.000 <0.05 which means that there is a significant influence between Tax Knowledge and gender on Tax Compliance of individual taxpayers. From the results of the determination coefficient analysis, it is known that the simultaneous contribution is 51.4%. It can be interpreted that Tax Knowledge between Women and men contributes Tax Compliance of 51.4% and the remaining 48.6% is determined by other factors that cannot be explainedKeyword : tax knowledge, gender, tax complianc, tax payer